Державний дендрологічний парк “Олександрія” НАН України: історія та сьогодення - Galkin, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
On the basis of archival materials the history of the creation of the park Alexandria and the main stages of building on an extent more than 200 years are studied. Process of its formation as research establishment after submission in 1946 of academy of sciences of Ukraine is considered. Are summed up introduction of the plants, the characteristic of scientific thises is made and the basic directions of the further scientific researchers are defined.